Answer:
The frequency of the oscillations in terms of fo will be f2=fo/3
E xplanation:
T=
![2pie\frac sqrt {m}{k}](https://img.qammunity.org/2021/formulas/physics/high-school/hsl4af0o9amuw4z8dfsyzzlxx65ic04b0i.png)
=1:3
⇒f2=fo\3
Here frequency f is inversely poportional to square root of mass m.
so the value of remainder of frequency f2 and fo is equal to 1:3.
⇒
=
![\frac sqrt{m1}[m2}](https://img.qammunity.org/2021/formulas/physics/high-school/yxbcczs6w92hbbx29r0hn15sxhkqo05wzr.png)
⇒
= 1:3
⇒f2=
![\frac{fo} {3}](https://img.qammunity.org/2021/formulas/physics/high-school/47kebr4n95iprz6ye2p3bl8rab7xkeb798.png)